Working memory capacity and the development of L2 speech production: and exploratory study - Weissheimer, Janaina (2007)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente